2019
DOI: 10.21475/ajcs.19.13.08.p1609
|View full text |Cite
|
Sign up to set email alerts
|

Glauconitic siltstone as a multi-nutrient fertilizer for Urochloa brizantha cv. Marandú

Abstract: Potassium (K) is one of the most absorbed nutrients by forage plants and it is found at low levels in tropical soils, requiring large amounts of fertilizers. The use of glauconitic siltstone as multi-nutrient fertilizers is an economic alternative to improve pasture-based production systems due to their low-cost production and long-term nutrient release. This study evaluated the effect of the glauconitic siltstone (GS) powder on three successive crops of Urochloa brizantha cv. Marandú (Syn. Brachiaria brizanth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…To optimize the efficiency of the use of these rocks and take advantage of their potential to supply K content to plants (Violatti et al, 2019;Arrieta et al, 2020), processes such as grinding to increase the contact surface with the soil, calcined at different temperatures with or without the addition of flux such as CaO that alters the crystalline structure of the minerals, the acidification with acids of low molecular weight associated with incubation times or even the mixture of rocks with organic matrices rich in K 2 O such as coffee husk, could demonstrate positive results in the solubility and K 2 O release capacity from the mineral matrices (Martins et al, 2015;Pessoa et al, 2015;Santos et al, 2015).…”
Section: _______________________________________________mentioning
confidence: 99%
“…To optimize the efficiency of the use of these rocks and take advantage of their potential to supply K content to plants (Violatti et al, 2019;Arrieta et al, 2020), processes such as grinding to increase the contact surface with the soil, calcined at different temperatures with or without the addition of flux such as CaO that alters the crystalline structure of the minerals, the acidification with acids of low molecular weight associated with incubation times or even the mixture of rocks with organic matrices rich in K 2 O such as coffee husk, could demonstrate positive results in the solubility and K 2 O release capacity from the mineral matrices (Martins et al, 2015;Pessoa et al, 2015;Santos et al, 2015).…”
Section: _______________________________________________mentioning
confidence: 99%
“…Later, Lima et al (2007) detailed the Serra da Saudade Formation lithotypes and the genesis of the phosphatic mineralization. The São Gotardo region was studied by Moreira et al (2016), who described the glauconitic siltstone unit with K 2 O concentrations of up to 10 wt%, used to produce potash fertilizers (Violatti et al 2019).…”
Section: Geological Backgroundmentioning
confidence: 99%
“…4E), which is responsible for a whole-rock K 2 O content of approximately 10 wt% (Nader and Ackroyd 2017, Moreira et al 2016Moreira et al , 2020. Although innumerous studies regard the evaluation of the green siltstone ("verdete") as potassium source for agriculture (Piza et al 2011), up until recently, only the glauconitic siltstone was confirmed to be a fertilizer (Violatti et al 2019). Both the green and the glauconitic siltstones were deposited by settling in an outer shelf context, in the absence of energy.…”
Section: Green and Glauconitic Siltstonesmentioning
confidence: 99%
“…It is mostly composed of glauconite mineral (40-80%), K-feldspar (10-15%), quartz (10-60%), and muscovite (5%) (Moreira et al, 2016). Glauconitic siltstone is a promising K fertilizer, with about 10% K 2 O (Violatti et al, 2019). The production process for glauconitic siltstone fertilizers is based on mechanical activation technology (Singla et al, 2019).…”
Section: Introductionmentioning
confidence: 99%